Lessons learned from the evaluation of Helen Keller International’s enhanced homestead food production program - Olney, Deanna K.; Dillon, Andrew; Ruel, Marie T.; Nielsen, Jennifer (International Food Policy Research Institute, 2016)
This chapter summarizes the primary results from the impact evaluation and two rounds of process evaluation described above that have been previously published in journal articles (van den Bold et al. 2015; Olney et al. 2015, 2016) or program evaluation reports (Olney, Behrman, et al. 2013; Dillon et al. 2012). The chapter brings together these different findings to describe the overall impacts that HKI’s EHFP program in Burkina Faso had on maternal and child health, nutrition, and well-being outcomes during the program period, and discusses how these impacts may have been achieved along the hypothesized program impact pathways. In addition, we discuss ideas about how this type of program could be further leveraged to optimize impacts on maternal and child health, nutrition, and well-being outcomes in future programs.